2017
DOI: 10.2147/ijwh.s128517
|View full text |Cite
|
Sign up to set email alerts
|

Maternal experiences with and sources of information on galactagogues to support lactation: a cross-sectional study

Abstract: An increase in the marketing and use of herbal galactagogues among breastfeeding mothers in the US has raised the issue of how best to provide support and information on the use of these products, particularly in light of limited availability of certified lactation counselors and continued suboptimal rates of breastfeeding globally. Currently, no cross-sectional data are available on the experiences and attitudes of mothers regarding the use of herbal and pharmaceutical galactagogues for lactation in the US. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
4
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 67 publications
10
49
4
4
Order By: Relevance
“…Consistent with previous reports, the use of T/CM in this study was associated with personal preference and a perception that such products are natural, safer and with fewer side effects than conventional treatments [13,28,41,42]. Interestingly, in this study the number of women who perceived T/CM to be safe was substantially lower than those who reported using T/CM during lactation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with previous reports, the use of T/CM in this study was associated with personal preference and a perception that such products are natural, safer and with fewer side effects than conventional treatments [13,28,41,42]. Interestingly, in this study the number of women who perceived T/CM to be safe was substantially lower than those who reported using T/CM during lactation.…”
Section: Discussionsupporting
confidence: 89%
“…Breastfeeding women should be made aware of the risks and benefits before they can make an informed decision about using T/CM when necessary. Two recent studies involving this population reported breastfeeding mothers may experience adverse reactions ranging in severity from mild to serious, including nausea, vomiting, and decreased glucose levels [28,49]. More extreme cases such as toxic epidermal necrolysis was linked to the use of Trigonella foenum-graecum by a young woman [50] and a precaution is warranted for cross-reaction among Trigonella foenum-graecum and chickpeas, peanuts, and other legumes in allergic patients is possible [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В то же время многие респонденты сообщили о том, что воспринимают ЛС как бесполезные. Авторы делают вывод, что необходи-мы дополнительные доказательства безопасности и эффективности, чтобы правильно информировать жен-щин, которые их используют [46]. Этими же авторами годом ранее [37] в результате опроса было выявлено, что более 70% медработников и консультантов по ГВ в США рекомендуют лактогонные средства.…”
Section: в исследованияхunclassified
“…При этом фенхель занимает первое место среди растительных лактогонных средств по частоте назначения в Швейцарии -80% [41], а также второе место после пажитника в США [46]. Причем авторы отмечают, что 16% (29 человек из 188 проживающих в США) из опрошенных применяли фен-хель, 58% не были уверены, что количество молока уве-личилось при приеме, однако при этом 79% из них сооб-щили, что будут использовать фенхель повторно, 76% рекомендовали бы его использование другим, и только 5 человек не стали бы его рекомендовать из-за неэффек-тивности, большинство (55,2%) сообщили о высоком уровне безопасности фенхеля, только 6 человек сооб-щили о неуказанных побочных эффектах.…”
Section: в исследованияхunclassified